Programa Mulheres Mil no IFCE Campus de Limoeiro do Norte: uma análise da inserção no mercado de trabalho das egressas, uma possibilidade de protagonismo feminino ou um reforço do papel tradicionalmente destinado às mulheres? - Melo, Marcela da Silva (2019)
This study analyzed the National Thousand Women Program as a training tool for the insertion in the labor market of women considered to be socially vulnerable, with the aim of achieving emancipation, protagonism and female empowerment through productive inclusion. Its general objective was to evaluate the National Thousand Women Program from the perspective of insertion of graduates in the labor market and its implications for female empowerment, from the courses offered by IFCE Campus of Limoeiro do Norte. The specific objectives intended to analyze the conceptual and methodological bases of the program in relation to the economic, political and social context and its application; raise the circumstances of policy implementation and development at the IFCE Campus of Limoeiro do Norte; identify the forms and types of insertion of graduates in the labor market; and, finally, to understand the egresses' perceptions regarding the implications of the program for their emancipation, protagonism and empowerment. To achieve the proposed objectives, the Depth Assessment Methodology was used as an evaluative perspective, in its content, context and institutional trajectory dimensions. This methodology is based on the qualitative research. For data collection, we used semi-structured interviews and focus group with the graduates and managers of IFCE, which offer greater interaction with the research subjects, in addition to the analysis of institutional documents. Data analysis was based on content analysis. In order to ground the study, theoretical assumptions were adopted that clearly guided the categories of analysis: the intricacies of capitalism that have altered and submitted the function of social protection of the state, precarious the contemporary labor market, deepened the sexual division of gender and the dialectic inclusion / exclusion.